2021
DOI: 10.1002/smll.202008148
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophilic Ni‐based Multicomponent Nanorod‐Confined‐Nanoflake Array Electrode Achieves Waste‐Battery‐Driven Hydrogen Evolution and Hydrazine Oxidation

Abstract: The low thermodynamic potential (−0.33 V) and safe by‐product of N2/H2O, make utilizing hydrazine oxidation reaction (HzOR) to replace thermodynamically‐unfavorable and kinetically‐sluggish oxygen evolution reaction a promising tactic for energy‐efficient hydrogen production. However, the complexity of bifunctionality increases difficulties for effective material design, thus hindering the large‐scale hydrogen generation. Herein, we present the rationally designed synthesis of superhydrophilic Ni‐based multico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…Supporting Information), indicating the significantly improved HzOR activity by doping Ru SAs in WS 2 , which implies the important role that Ru atoms take in the HzOR and Ru sites may be the main active centers for HzOR (Figure 5b). The attractive working potential of HzOR for CC@WS 2 /Ru-450 outperforms the other recently reported counterpart catalysts such as Mo-Ni 3 N/Ni/NF (−0.3 mV) [2] and Ni NCNAs (−26 mV) [57] (Figure 5g), etc. The detailed working potentials for each catalyst are provided in Table S3 of the Supporting Information.…”
Section: Investigation Of Electrochemical Hzor Performancementioning
confidence: 62%
“…Supporting Information), indicating the significantly improved HzOR activity by doping Ru SAs in WS 2 , which implies the important role that Ru atoms take in the HzOR and Ru sites may be the main active centers for HzOR (Figure 5b). The attractive working potential of HzOR for CC@WS 2 /Ru-450 outperforms the other recently reported counterpart catalysts such as Mo-Ni 3 N/Ni/NF (−0.3 mV) [2] and Ni NCNAs (−26 mV) [57] (Figure 5g), etc. The detailed working potentials for each catalyst are provided in Table S3 of the Supporting Information.…”
Section: Investigation Of Electrochemical Hzor Performancementioning
confidence: 62%
“…Furthermore, electrocatalytic HzOR provides a possible pathway for removing hydrazine from industrial sewage, which is expected to bring significant benefits in not only industrial sewage degradation but also energy-saving hydrogen production. Based on the foregoing, Li et al [16] built three-dimensional (3D) hierarchical arrays (Ni NCNA) onto nickel foam for hydrazine oxidation-assisted hydrogen evolution, achieving a much lower voltage of only 0.124 V to afford 100 mA cm −2 in the assembled two-electrode system, which is 1.583 V lower than that of the corresponding overall water splitting (OWS) system. Despite these exciting breakthroughs in pure alkaline water, some unprecedented challenges in the alkaline seawater system remain to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the oxidation of thermodynamically favorable organic small molecules, such as urea, 25–27 hydrazine, 28–30 ethanol, 31,32 and 5-hydroxymethylfurfural, 33,34 instead of the oxygen evolution reaction, can effectively improve the anode reaction efficiency and achieve hydrogen production at a lower voltage. Among them, the hydrazine oxidation reaction (HzOR) has gotten a lot of attention because of its low theoretical oxidation potential (−0.33 V vs. RHE), safe and pollution-free byproduct (N 2 H 4 + 4OH − → N 2 + 4H 2 O + 4e − ), and adaptiveness to a separator free electrolyzer.…”
Section: Introductionmentioning
confidence: 99%